ABHD6 loss-of-function in mesoaccumbens postsynaptic but not presynaptic neurons prevents diet-induced obesity in male mice - David Lau; Stephanie Tobin; Horia Pribiag; Shingo Nakajima; Alexandre Fisette; Dominique Matthys; Anna Kristyna Franco Flores; Marie-Line Peyot; S. R. Murthy Madiraju; Marc Prentki; David Stellwagen; Thierry Alquier; et al. (Nature Communications)
Abstract α/β-hydrolase domain 6 (ABHD6) is a lipase linked to physiological functions affecting energy metabolism. Brain ABHD6 degrades 2-arachidonoylglycerol and thereby modifies cannabinoid receptor signalling. However, its functional role within mesoaccumbens circuitry critical for motivated behaviour and considerably modulated by endocannabinoids was unknown. Using three viral approaches, we show that control of the nucleus accumbens by neuronal ABHD6 is a key determinant of body weight and reward-directed behaviour in male mice. Contrary to expected outcomes associated with increasing endocannabinoid tone, loss of ABHD6 in nucleus accumbens, but not ventral tegmental area, neurons completely prevents diet-induced obesity, reduces food- and drug-seeking and enhances physical activity without affecting anxiodepressive behaviour. These effects are explained by attenuated inhibitory synaptic transmission onto medium spiny neurons. ABHD6 deletion in nucleus accumbens neurons and dopamine ventral tegmental area neurons produces contrasting effects on effortful responding for food. Intraventricular infusions of an ABHD6 inhibitor also restrain appetite and promote weight loss. Together, these results reveal functional specificity of pre- and post-synaptic mesoaccumbens neuronal ABHD6 to differentially control energy balance and propose ABHD6 inhibition as a potential anti-obesity tool.